2022
DOI: 10.1186/s12884-022-04737-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carotenoid intake and risk of developing preeclampsia: a hospital-based case–control study

Abstract: Background The effect of carotenoids on the risk of preeclampsia (PE) is uncertain. We aimed to examine the associations between the intake of dietary carotenoids and related compounds by pregnant women in China, and the risk of their developing PE. Methods Four hundred and forty PE cases and 440 age- (± 3 years), gestational age- (± 1 weeks) and gestational diabetes mellitus status- (yes/no) matched healthy controls were recruited from March 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Generally, it is asserted that lycopene can be used as a safe dietary supplement during pregnancy and lactation [ 234 ]. Although in pregnant women, high dietary intake of lycopene has shown to mitigate the risk of developing preeclampsia [ 235 ]. Imran et al [ 7 ] reported that excessive chronic consumption of tomato juice, a rich source of lycopene, caused lycopenemia.…”
Section: Lycopene: Safety and Potential Toxicitymentioning
confidence: 99%
“…Generally, it is asserted that lycopene can be used as a safe dietary supplement during pregnancy and lactation [ 234 ]. Although in pregnant women, high dietary intake of lycopene has shown to mitigate the risk of developing preeclampsia [ 235 ]. Imran et al [ 7 ] reported that excessive chronic consumption of tomato juice, a rich source of lycopene, caused lycopenemia.…”
Section: Lycopene: Safety and Potential Toxicitymentioning
confidence: 99%
“…Some studies have shown that VA and VE supplementation during pregnancy can protect against PE (18)(19)(20)(21). Our previous studies have found that dietary carotenoid intake is associated with PE risk (22). In contrast, some studies have suggested that there is no association between the risk of gestational hypertensive disorders and dietary VE intake (23).…”
Section: Introductionmentioning
confidence: 99%